Interdisciplinary connections to special education key related professionals involved - Obiakor, Festus E.; Bakken, Jeffrey P. (Advances in special education, 2015)
This two-part volume addresses the specific area of interdisciplinary connections within special education research. Special education has transformed as a result of legislation, new trends and current research investigations. Currently, there is no comprehensive resource that effectively covers these advances. Continuing the approach of part a, part b allows readers to follow interdisciplinary connections within special education as it relates to the roles of audiologists, surgeons, vision specialists and school nurses.